Can We Detect Chronic Pancreatitis With Low Serum Pancreatic Enzyme Levels?. Issue 8 (September 2016) - Kwon, Chang-Il; Kim, Hong Joo; Korc, Paul; Choi, Eun Kwang; McNulty, Gail M.; Easler, Jeffrey J.; El Hajj, Ihab I.; Watkins, James; Fogel, Evan L.; McHenry, Lee; Zimmerman, Michelle K.; Sherman, Stuart; et al.
Abstract : Objectives: The aims of this study were to evaluate whether serum pancreatic enzyme levels could be used to aid screening for chronic pancreatitis (CP). Methods: 170 healthy volunteers were screened and prospectively enrolled in the control group. 150 patients who were diagnosed with calcific CP were enrolled in the patient group by retrospective review. Serum amylase and lipase levels were compared between the 2 groups. Results: The mean values ± SD of the control group were compared with those of the patient group for serum amylase level (48.1 ± 13.2 vs 34.8 ± 17.2 U/L, P < 0.001) and serum lipase level (26.4 ± 11.3 vs 16.3 ± 11.2 U/L, P < 0.001). On the receiver operating characteristic curve analysis for amylase level, area under the curve was 0.740 (95% confidence interval), and sensitivity and specificity were 38.7% and 94.1%, respectively, with a cutoff value of 27.5 U/L. On the receiver operating characteristic curve analysis for lipase level, area under the curve was 0.748 (95% confidence interval), and sensitivity and specificity were 33.3% and 95.9%, respectively, with a cutoff value of 10.5 U/L. Conclusions: Our results suggest that low serum pancreatic enzyme levels can be used to aid in detection of CP.